2001
DOI: 10.1080/110241501750070547
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Injury after Blunt Abdominal Trauma

Abstract: Because delay in diagnosis is significantly associated with morbidity and duration of hospital stay we recommend that all patients admitted with blunt abdominal trauma should have a diagnostic peritoneal lavage as soon as possible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In a series reporting 333 cases of blunt abdominal trauma including 31 mesenteric injuries, 30 of these were small bowel devascularisation with only four large bowel devascularisation injuries [7]. Cripps and Cooper reported that small bowel injuries were associated with high velocity impacts irrespective of the degree of abdominal compression, while large bowel injuries occur at both high and low velocity impacts associated with abdominal compression [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a series reporting 333 cases of blunt abdominal trauma including 31 mesenteric injuries, 30 of these were small bowel devascularisation with only four large bowel devascularisation injuries [7]. Cripps and Cooper reported that small bowel injuries were associated with high velocity impacts irrespective of the degree of abdominal compression, while large bowel injuries occur at both high and low velocity impacts associated with abdominal compression [8].…”
Section: Discussionmentioning
confidence: 99%
“…Management entails operative exploration once a diagnosis of small bowel obstruction is made. It is well documented that early operation improves survival and decreases morbidity ( 6 , 13 , 14 ). Our patient benefited from immediate CT scans and operative intervention by minimal bowel resection with subsequent discharge to his normal environment and occupation.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate for EOR versus DOR was reported in nine studies (20)(21)(22)(23)(24)(25)(26)(27)(28). Overall, 1,008 and 404 patients received EOR and DOR, respectively.…”
Section: -Complication Ratementioning
confidence: 99%
“…Length of stay was reported in 4 studies (20,22,26,28) for EOR versus DOR. Overall, 434 and 268 patients respectively received EOR and DOR.…”
Section: -Length Of Staymentioning
confidence: 99%